Edukasi Sistem Informasi Akuntansi Sederhana sebagai Upaya Meningkatkan Transparansi dan Akuntabilitas Koperasi - Pratama, Ibrahim; Trisnawaty, Trisnawaty; Kahfi, Zul; Nurhasanah, Andi Nurhasanah; Azhari, Sri Rahayu Indah (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2025)
This Community Service (PkM) activity aims to enhance the transparency and accountability of cooperative financial management through the implementation of a Simple Accounting Information System (SAIS) in several active cooperatives in Takalar Regency. The primary challenges faced by these cooperatives include manual financial record-keeping, susceptibility to errors, and a lack of accurate report availability, which hinders decision-making and erodes member trust. The service methodology employs a Participatory Action Research (PAR) approach, involving an initial survey, SAIS design based on spreadsheets, intensive training, and implementation assistance for eight core cooperative administrators. Data was collected through interviews, observations, and questionnaires administered to twelve active members. The activity's results indicate that cooperative administrators are able to operate the SAIS independently, producing monthly financial reports that were previously difficult to generate. The implementation of SAIS significantly improved members' perceptions of cooperative transparency and accountability, evidenced by easier access to information and an increase in trust. This success suggests that appropriate technology, even when simple, can be effective in improving cooperative financial governance and strengthening the foundation of trust. It is hoped that the outcomes of this PKM can serve as a replication model for other cooperatives in Takalar Regency to achieve more professional and sustainable financial management.